The house of hidden letters - Broom, Isabelle, 1979- (Berkley, 2026)
"Skye MacKinnon is desperate for an escape. When she wins a lottery to buy a run-down cottage on a Greek island for only one euro, Skye jumps at the chance to get out of England and start over. As she unlocks the tattered blue door of her whitewashed new cottage, the sun-kissed sea glinting in the bay outside her windows, Skye immediately feels like she's found her true home. Skye and the other lottery winners--the first residents in these houses since the 1940s--form a tight-knit group, finding in one another the strong relationships they'd been missing in their own lives. When Skye and local contractor Andreas discover a set of mysterious letters, they begin to unravel the history of the prior residents and the truth about life on Folegandros during the Second World War"-- Provided by publisher.